A Collective Impact Approach To The Reading Achievement Gap. Issue 6 (18th August 2018) - Pasini, Nicole
Abstract: This essay profiles The Big Lift, a multi-agency initiative to improve third-grade reading proficiency in San Mateo County, California. The Big Lift is an example of collective impact, in which organizations from different sectors unite around a common agenda to solve a social challenge. This kind of initiative goes beyond collaboration, requiring its own infrastructure, dedicated staff, ongoing communication and shared measurements of success. Library participation is critical to the success of community and literacy-focused collective impact projects like The Big Lift.